Pengaruh Model Pembelajaran Problem Based Learning Berbantuan LKS terhadap Keterampilan Proses Sains Siswa SMP Negeri 1 Lape Kabupaten Sumbawa - Hidayah, Fitri; Royani, Ida (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2021)
The success in learning Biology can be seen from the cognitive abilities of students, but a low average score is an indication of difficulties in students' science process skills skills related to ecosystem material. This study aims to determine the effect of the problem based learning model assisted by student worksheets (LKS) on students' science process skills. The research design used was quasi-experimental in the form of one-group pretest-posttest design. The population in this study were all class VIII, while the sample selected was class VIIIA as the experiment class. This sample was determined using a saturated sampling technique. Data regarding science process skills were taken using the pretest-postest instrument in the form of essay questions. Before further analyzing the pretest-postest results, the two classes were first tested for normality and homogeneity. The results of the hypothesis test show that = 13,646> = 1,734 which means that Ho is rejected, so that there is a difference between the experimental class science process skills on the posttest and pretest results or in other words there is an effect of the learning model of problem based learning assisted by LKS on students' science process skills. This indicates that learning with a learning model of problem based learning assisted by student worksheets allows students to achieve science process skills.